28. THE EFFICACY OF AURICULAR ACUPUNCTURE FOR INSOMNIA IN POST-STROKE PATIENTS: A RANDOMIZED, DOUBLE-BLIND, CONTROLLED TRIAL (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the efficacy of auricular acupuncture in treating insomnia in the late recovery or chronic phase following a stroke.Subject and method: This is a randomized, double-blind, controlled clinical trial conducted on 60 post-stroke patients with insomnia at the Ho Chi Minh City Traditional Medicine Hospital from December 2023 to June 2024. Patients were randomly assigned to two groups: the study group (auricular acupuncture + standard treatment) and the control group (sham auricular acupuncture + standard treatment). Sleep indices were monitored and assessed using the PSQI score at 0, 5, 10, 15, and 30 days.Results: After 30 days, the study group showed significant improvements in sleep onset latency (1.27 ± 0.45 and 1.60 ± 0.62 in the control group, p
Keywords: Nhĩ châm; mất ngủ sau đột quỵ; PSQI